2007
DOI: 10.1209/0295-5075/78/46007
|View full text |Cite
|
Sign up to set email alerts
|

On the temperature dependence of thermal diffusion of liquid mixtures

Abstract: Concentration-and temperature-dependent measurements of the Soret coefficient ST have been performed for binary mixtures containing benzene and cyclohexane, both of different degrees of deuteration, and dibromohexane. They are discussed together with data on ethanol/water, toluene/n-hexane, and benzene in heptane, tridecane, and 2,2,4-trimethylpentane taken from the literature. ST can be negative or positive and change its sign both as a function of concentration and temperature. For all systems the Soret coef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
52
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 24 publications
5
52
0
Order By: Relevance
“…[20][21][22][23][24][25] It has been revealed that a sign of S T of the polymer in solution can occur as function of the solution temperature as well as of the solvent composition. [26][27][28][29][30] For liquid mixtures composed of small molecules thermally induced sign change of S T have been studied by several researchers [31][32][33][34] , sometime those sign changes could be correlated with structural changes in the liquid mixtures. For polymer solutions and colloidal suspensions sometimes sign changes occur und bad solvent conditions.…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22][23][24][25] It has been revealed that a sign of S T of the polymer in solution can occur as function of the solution temperature as well as of the solvent composition. [26][27][28][29][30] For liquid mixtures composed of small molecules thermally induced sign change of S T have been studied by several researchers [31][32][33][34] , sometime those sign changes could be correlated with structural changes in the liquid mixtures. For polymer solutions and colloidal suspensions sometimes sign changes occur und bad solvent conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Only in the case of polar acetone ∆S T is approximately 30% larger but still concentration independent. This investigation has also been extended to a broader temperature range 27 .…”
Section: Introductionmentioning
confidence: 99%
“…The benzene concentration at which S T changes its sign increases with temperature. The dibromohexane/cyclohexane mixture [185] can also be attributed to this group, while S T does not change its sign with concentration.…”
Section: Temperature Dependence Of the Soret Coefficientmentioning
confidence: 81%
“…Generally, it was applied to different kind of mixtures: simple fluid mixtures [36,113,75,111,183,185] polymer solutions [34,72,123], micellar solutions [109,110] and colloidal dispersions [33,106]. The advantages of the method are a small temperature difference (∼20 µK) and a small fringe spacing (∼20 µm) which keeps the system close to the thermal equilibrium and allows also the investigation of slow diffusing systems such as polymers and colloids.…”
Section: Thermal Diffusion Forced Rayleigh Scatteringmentioning
confidence: 99%
See 1 more Smart Citation